2020
DOI: 10.1002/app.49694
|View full text |Cite
|
Sign up to set email alerts
|

Trifunctional quinoxaline‐based maleimide and its polymer alloys with benzoxazine: Synthesis, characterization, and properties

Abstract: Novel quinoxaline-based trismaleimide (2,3-di[3-maleimido]phenyl-6-maleimidoquinoxaline, namely TQMI) and its polymer alloys with 3-phenyl-3,4dihydro-2H-1,3-benzoxazine (P-a) were successfully prepared and characterized. Differential scanning calorimetry investigation of TQMI exhibited distinct double exothermic peaks, which implied that the curing behavior of different type of maleimide group was discrepant. The curing temperature of P-a/TQMI prepolymers was lower than that of both neat TQMI and P-a monomer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The T d 5% 's and char yields at 600°C in N 2 are representative for conventional bismaleimide thermosets 30 . The typical curing temperature of the maleimides (<250°C), 19 is considerably lower than the decomposition temperatures of all oligomers, suggesting the oligomers are thermal stable and the cure temperature is safe to operate for all oligomers.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The T d 5% 's and char yields at 600°C in N 2 are representative for conventional bismaleimide thermosets 30 . The typical curing temperature of the maleimides (<250°C), 19 is considerably lower than the decomposition temperatures of all oligomers, suggesting the oligomers are thermal stable and the cure temperature is safe to operate for all oligomers.…”
Section: Resultsmentioning
confidence: 96%
“…Conventional experimental techniques such as DSC, 36–38 FTIR, 19 and UV‐reflection spectroscopy 39 can be used to characterize the cure of maleimides, with isothermal and non‐isothermal techniques. Studies have shown that curing of maleimide follows first order kinetics with an activation energy of ~100 kJ/mol 40,41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curing temperature, curing time, curing degree, and curing reaction rate are important parameters in the process of material processing 43 . The curing reaction can be carried out depends on the apparent activation energy of the curing reaction system, and the apparent activation energy directly reflects the degree of difficulty in the polymerization of the resin system 44 . Therefore, the study on the curing power of MB‐FH monomers, the relationship between the curing process and product properties, and the optimization of curing process conditions have attracted extensive attention from the scholars.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] For improving the performance of benzoxazine resins and expanding their application in the field, a large number of researchers have done a lot of research work on the modification of benzoxazine resin. [17][18][19][20][21][22] It is a very important method in improving the properties of benzoxazine resin by blending or copolymerizing. [23][24][25][26][27][28][29][30] By blending or copolymerizing, the crosslinking density of polybenzoxazine resin can be effectively increased, and the mechanical properties and thermal stability of the polymer can be significantly improved.…”
Section: Introductionmentioning
confidence: 99%